Antifungal Activity and Phytochemical Screening of Anisochilus carnosus (L) Wall and Melaleuca alternifolia (Maiden & Betche) against opportunistic pathogen Candida albicans - M, Palaniswamy. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT This paper deals with the antifungal and phytochemical studies of Anisochilus carnosus (L) Wall and Melaleuca alternifolia (Maiden & Betche) against opportunistic pathogen Candida albicans. The medicinal plants selected for the study were collected from Navamalai, Pollachi, India. The plant extracts showed a wide range antifungal activity. The results were supported by phytochemical analysis.